The Effect Of Organizational Support On Teachers’ Adaptive Performance With Innovative Work Behavior As A Mediating Variable: (Study At High School In The Zoning Of Palangka Raya-1) - Qovif Indah Purnama Putri; Nurlia Eka Damayanti (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2023)
Objectives – This study aims to determine the effect of organizational support on teachers' adaptive performance with innovative work behavior as a mediating variable.Design/Methodology/Approach – The research method used in this research is descriptive statistics using a quantitative approach. The collected data were analyzed using the Structural Equation Modeling (SEM) approach with the Partial Least Square (PLS) approach. The software used was SmartPLS 3.Findings – The results showed that: the role of innovative work behavior was able to fully mediate the effect of organizational support on adaptive performance, organizational support had no significant positive effect on adaptive performance, organizational support has a significant positive effect on innovative work behavior, and innovative behavior has a significant positive effect on the adaptive performance for teacher of high school in the zoning of Palangka Raya-1.